Real-life resilience: Exploring the organisational environment of international water utilities. (December 2022) - Giffoni, Eduarda; Jude, Simon; Smith, Heather M.; Pollard, Simon J.T.
Abstract: The water sector has signalled the need to advance organisational and social resilience efforts. There is a lack of understanding of whether the organisational environment in water utilities is conducive to organisational resilience. Themes from interviews showcased challenges related to cognitive and contextual organisational properties. We identified a need to broaden the cognitive frame of utilities to account for flexible concepts of enhanced sense-making. We propose categories of organisational silos and a set of cultural attributes that contribute to organisational resilience. Interventions are needed to develop the cognitive, behavioural, and contextual properties of utilities that support organisational resilience. Highlights: Understanding the reality of utilities with regard to resilience is needed. Interviews with international water and wastewater utility managers were conducted. Challenges were predominantly related to cognitive and contextual properties. The current cognitive frame inhibits enhanced sense-making toward preparedness. Different categories of silos hinder the development of contextual properties.